Looking for Options to Sustainably Fixate Nitrogen. Are Molecular Metal Oxides Catalysts a Viable Avenue? - González-Cabaleiro, Rebeca; Thompson, Jake A.; Vilà-Nadal, Laia (Frontiers in Chemistry, 2021)
The fast and reliable industrial production of ammonia (NH3) is fundamentally sustaining modern society. Over the past 20 years, scientists have imagined the possibility of developing a milder synthesis of ammonia by mimicking the nitrogenase enzyme, which fixes nitrogen from the air at ambient temperatures and pressures to feed leguminous plants. To do this, we propose the use of highly reconfigurable molecular metal oxides or polyoxometalates (POMs). Our proposal is an informed design of the polyoxometalate after exploring the catabolic pathways that cyanobacteria use to fix N2 in nature, which is a different route than the one followed by the Haber–Bosch. Meanwhile, the industrial process is a ‘brute force’ system towards breaking the triple bond N-N, needing high pressure and high temperature to increase the rate of reaction, nature first links the protons to the N2 to the later easier breaking of the triple bond at environmental temperature and pressure. Computational chemistry data on the stability of different polyoxometalates will guide us to decide the best design for a catalyst. Testing the reductio of N2 with different catalysts in the laboratory conditions will allow for a sustainable reactor design of small-scale production.